The Non-amyloidal Component Region of α-Synuclein Is Important for α-Synuclein Transport Within Axons - Anderson, Eric N.; Hirpa, Delnessaw; Zheng, Kan Hong; Banerjee, Rupkatha; Gunawardena, Shermali (Frontiers in Cellular Neuroscience, 2020)
Proper transport of the Parkinson’s disease (PD) protein, α-synuclein (α-syn), is thought to be crucial for its localization and function at the synapse. Previous work has shown that defects in long distance transport within narrow caliber axons occur early in PD, but how such defects contribute to PD is unknown. Here we test the hypothesis that the NAC region is involved in facilitating proper transport of α-syn within axons via its association with membranes. Excess α-syn or fPD mutant α-synA53T accumulates within larval axons perturbing the transport of synaptic proteins. These α-syn expressing larvae also show synaptic morphological and larval locomotion defects, which correlate with the extent of α-syn-mediated axonal accumulations. Strikingly, deletion of the NAC region (α-synΔ71–82) prevented α-syn accumulations and axonal blockages, and reduced its synaptic localization due to decreased axonal entry and axonal transport of α-syn, due to less α-syn bound to membranes. Intriguingly, co-expression α-synΔ71–82 with full-length α-syn rescued α-syn accumulations and synaptic morphological defects, and decreased the ratio of the insoluble higher molecular weight (HMW)/soluble low molecular weight (LMW) α-syn, indicating that this region is perhaps important for the dimerization of α-syn on membranes. Together, our observations suggest that under physiological conditions, α-syn associates with membranes via the NAC region, and that too much α-syn perturbs axonal transport via aggregate formation, instigating synaptic and behavioral defects seen in PD.